A novel drug delivery system of mixed micelles based on poly(ethylene glycol)‐poly(lactide) and poly(ethylene glycol)‐poly(ɛ‐caprolactone) for gambogenic acid - Tong‐Yuan Lin; Ting‐Ting Zhu; Yan Xun; Yun‐Song Tao; Yu‐Qin Yang; Jia‐Li Xie; Xiao‐Ming Zhang; Shi‐Xiong Chen; Bai‐Jing Ding; Wei‐Dong Chen (Kaohsiung Journal of Medical Sciences, 2019)
Abstract In this study, a novel mixed polymeric micelles formed from biocompatible polymers, poly(ethylene glycol)‐poly(lactide) (mPEG‐PLA) and poly(ethylene glycol)‐poly(ɛ‐caprolactone) (mPEG‐PCL), used as a novel nanocarrier to encapsulate gambogenic acid (GNA). GNA‐loaded mixed polymeric micelles (GNA‐MMs) was prepared by cosolvent evaporation method. The mean average size of GNA‐MMs was (83.23 ± 1.06) nm (n = 3) and entrapment efficiency (EE%) of GNA‐MMs was (90.18 ± 2.59) % (n = 3) as well as (12.36 ± 0.64) % (n = 3) for drug loading (DL%). Transmission electron microscopy revealed that the GNA‐MMs were spherical with “core‐shell” structures. Compared with free GNA solution, in vitro release of GNA from GNA‐MMs showed a two‐phase sustained release profile: an initial relatively fast phase and followed by a slower release phase. Pharmacokinetic results also indicated that the GNA‐MMs have longer systemic circulation time and slower plasma elimination rate than free GNA solution. Moreover, the in vitro cytotoxicity assay showed that the IC50 values on HepG2 cells for GNA‐MMs and free GNA were (5.67 ± 0.02) μM and (9.02 ± 0.03) μM, respectively. In addition, GNA‐MMs significantly increased the HepG2 cellular apoptosis in a concentration‐dependent manner. In conclusion, the results showed that mPEG‐PLA/mPEG‐PCL mixed micelles may serve as an ideal drug delivery system for GNA to prolong drug circulation time in body, enhance bioavailability and retained its potent antitumor effect.